Life cycle cost assessment of wind power–hydrogen coupled integrated energy system. (12th November 2019) - Fang, Ruiming
Abstract: Aiming at the economic evaluation of wind power-hydrogen coupled integrated energy system (WPHCIES), a life-cycle economic assessment method of integrated energy system is proposed. Firstly, the integrated scheme and operation mode of integrated energy system are given. Secondly, with the net profit of the integrated energy system in the whole life cycle as objectives and the energy flow and stable operation of the system as constraints, a mathematical model for the economic evaluation of the given integrated energy system in the whole life cycle is constructed, and the payback period and net profit of life cycle of the given system can be reckoned by the model. Finally, taking a wind farm in South China as background, the life cycle economic evaluation model of the proposed system is simulated and calculated, and the effects of both the ratio of hydrogen production from wind power and the ratio of hydrogen to fuel cell on the net profit of wind power-hydrogen coupled integrated energy system during the payback period and the whole life cycle are further analyzed. In addition, the comparison demonstrated that the capital return period of the wind farm can be reduced from 11 years to 8.13 years, and the cumulative net income can be increased from 0.67 billion yuan to 0.93 billion yuan by reasonably choosing the power ratio of hydrogen production from wind power. Highlights: A wind power-hydrogen coupled integrated energy system (WPHCIES)is proposed. A life cycle cost method is adopted to build the economic evaluation model of WPHCIES. Suitable capacity of electrolytic hydrogen system is important to WPHCIES. Fuel cell can smooth the fluctuating output of wind power with poor economic benefits.